2019
DOI: 10.3906/elk-1901-166
|View full text |Cite
|
Sign up to set email alerts
|

An automated snick detection and classification scheme as a cricket decisionreview system

Abstract: Umpire decisions can greatly affect the outcome of a cricket game. When there is doubt about the umpire's call for a decision, a decision review system (DRS) may be brought into play by a batsman or bowler to validate the decision. Recently, the latest technologies, including Hotspot, Hawk-eye, and Snickometer, have been employed when there is doubt among the on-field umpire, batsman, or bowlers. This research is a step forward in gaging the true class of a snick generated from the contact of the cricket ball … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…(16,17,26) Likewise, we found that, in cricket, figure skating and wushu, similar problems are evident, such as having an obsolete and tedious process for detecting sporting repercussions in games of these sports, as well as for modifying the score of game markers and for detection of movements of players as referees for the issuance of a precise judgment, this being the origin of the reason for their studies, which seek to detect the movements of sports objects and referees for the detection of game moments such as automating processes to updating game scores. (6,8,10,11,12,18,21,22,23,25) Likewise, in other sports such as basketball, hockey, fencing, handball, race-walking, skateboarding, we also find problems with presence in more than one sporting discipline, which lie in having a traditional approach for detecting sports incidents. (7,9,11,13,14,19,20) All…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…(16,17,26) Likewise, we found that, in cricket, figure skating and wushu, similar problems are evident, such as having an obsolete and tedious process for detecting sporting repercussions in games of these sports, as well as for modifying the score of game markers and for detection of movements of players as referees for the issuance of a precise judgment, this being the origin of the reason for their studies, which seek to detect the movements of sports objects and referees for the detection of game moments such as automating processes to updating game scores. (6,8,10,11,12,18,21,22,23,25) Likewise, in other sports such as basketball, hockey, fencing, handball, race-walking, skateboarding, we also find problems with presence in more than one sporting discipline, which lie in having a traditional approach for detecting sports incidents. (7,9,11,13,14,19,20) All…”
Section: Resultsmentioning
confidence: 91%
“…Ravi et al (22) Khan et al (23) Kamble et al (24) Shahjalal et al (25) Reno et al (26) Figure 3. Number of scientific publications this, in order to achieve precise decision making and a fair game, through event detection by having automated approaches for the detection and monitoring of players, balls and referee movements.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations